Safety management for products and packaging - Rajkiewicz, Mieczysław; Zwoliński, Łukasz (Wydawnictwa Politechniki Łódzkiej, 2015)
The paper outlines the general requirements of the health management system in the production of packaging for food products by PN EN 15593:2010. It also presents the survey results carried out among customers regarding their demand for product packaging and testing the level of knowledge of quality management systems and hygiene in production and packaging for food products.

W artykule przedstawiono ogólne wymagania systemu zarządzania bezpieczeństwem w produkcji opakowań do produktów spożywczych - PN EN 15593: 2010. Przedstawiono również wyniki badań przeprowadzonych wśród klientów dotyczących ich zapotrzebowania na opakowania produktów i poziomu wiedzy na temat systemów zarządzania jakością w produkcji i pakowaniu produktów spożywczych
Zarządzanie bezpieczeństwem produktów i opakowań
Keywords: organizacja i zarządzanie